Social Dynamics of the Families of Former Online Gamblers: Narrative Study of Former Online Gamblers in Wonomulyo District, Sidodadi Village, Polewali Mandar Regency - Alalwi, Ahmad Gazali; Kaharuddin, Kaharuddin; Jamaluddin, Jamaluddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine 1) Changes in social functions within a family after one of its members stops being an online gambler, and 2) The meaning of the status of